KINERJA KARYAWAN, APAKAH SUATU KEHARUSAN? [EMPLOYEE PERFORMANCE: IS IT A MUST?] - Suryawan, Ian Nurpatria; Ramadhani, Nanda Putri (Universitas Pelita Harapan, 2024)
This research aims to find out the effect of the independent variable (X), namely training, work discipline, and leadership style on the dependent variable (Y), namely employee performance at the PT. XYZ. The sampling technique used in this study was purposive sampling. Respondents involved in this study were 59 permanent employees. Data collection is done by spreading the spread. The method for analyzing the data in this study is multiple linear regression. Based on the hypothesis, the results of this study are that training, work discipline and leadership style have an effect on employee performance.Bahasa Indonesia Abstrak: Penelitian ini punya tujuan yang jelas untuk mengetahui pengaruh variabel bebas yakni gaya kepemimpinan, disiplin kerja, pelatihan pada variabel tergantung yakni kinerja karyawan di PT. XYZ. Teknik pengambilan sampel yang dipakai pada penelitian ini adalah purposive sampling. Responden yang terlibat pada penelitian sejumlah 59 orang karyawan tetap. Metode untuk analisa data pada penelitian yaitu regresi linear berganda. Sesuai pengujian hipotesis hasil dari penelitian ini yaitu pelatihan, disiplin kerja, gaya kepemimpinan memberi pengaruh pada kinerja karyawan.